A STUDY ON CUSTOMER SATISFACTION TOWARDS TITAN - Y, Esther Reeta (The journal of contemporary issues in business and government, 2021)
We use a large variety of goods and services in our daily life. These include items like toothpaste, toothbrush, soap, oil, clothes, food items, telephone, electricity and many more. How do all these goods and services reach our home? Obviously the business houses who produce the goods and services have to ensure that these are to be sold, and so they have to make the consumers/users aware of their products and place them at points convenient to the consumers. This involves a number of activities such as product planning, pricing, promotion, use of middlemen (wholesalers, retailer etc.) for sale, warehousing, transportation etc. All these activities taken together are termed as Marketing. In this lesson, we will learn about the concept of marketing, its importance, objectives and functions.